2008
DOI: 10.1117/1.2982534
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical microscopy of the bronchus

Abstract: Because of frequent exposure to carcinogens, the bronchus is prone to early pathologic alterations. The assessment of these early changes is of key significance in physiological studies and disease diagnosis of the bronchus. We utilize nonlinear optical microscopy (NLOM) to image mouse bronchial tissue based on intrinsic nonlinear optical contrast. Our results show that NLOM is effective for imaging the bronchial intact microstructural components, providing quantitative information about the biomorphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The approach for determining the spacing between elastic fibers has been described in our previous studies. 4 In this work, the spacing between elastic fibers in normal stroma is 14.13Ϯ 4.12 m ͑n =27 slices of 9 biopsies͒ and in neoplastic stroma is 1.72Ϯ 0.57 m ͑n =27 slices of 9 biopsies͒, indicating that the elastic fibers have a getting together tendency. Second, similar to the measurement of collagen, we also obtained the elastin area.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…The approach for determining the spacing between elastic fibers has been described in our previous studies. 4 In this work, the spacing between elastic fibers in normal stroma is 14.13Ϯ 4.12 m ͑n =27 slices of 9 biopsies͒ and in neoplastic stroma is 1.72Ϯ 0.57 m ͑n =27 slices of 9 biopsies͒, indicating that the elastic fibers have a getting together tendency. Second, similar to the measurement of collagen, we also obtained the elastin area.…”
mentioning
confidence: 87%
“…3 It is well suited for the observation of unstained samples based on intrinsic sources of nonlinear signals, 4 such as two-photon excited fluorescence ͑TPEF͒ and second-harmonic generation ͑SHG͒. It also has been used for in vivo cancer imaging.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it has been reported that the ratio of NADH over FAD°uorescence calculated by the equation, FAD 535 /(FAD 535 þNADH 475 Þ, is a parameter related to cellular metabolism. 15,16 In this study, the ratio of NADH over FAD°uorescence in ROI 1 region was 1:81 AE 0:03, which re°ected the metabolic state of chondrocytes and may be found application in characterization of pathological changes for distinguishing abnormal elastic cartilage from an intact one.…”
Section: Depth-resolved Spectral Imaging and Emission Spectra Of Elasmentioning
confidence: 91%